State Capture Through the Party System: the Collapse of Governance in Bosnia and Herzegovina (Balkan Politics: Political Parties in the Balkans, 1991-2024, 2025)
Bosnia and Herzegovina is perceived as a multiethnic state where ethnic groups occupy state’s posts. This system was established at Ryan Patterson military complex in Dayton, state Ohio in the USA. Based on the Dayton Peace Agree-ment (DPA) ethnic groups Bosniaks, Serbs and Croats have taken up state’s posts until today. The chapter “State Capture Through the Party System: The Collapse of Governan-ce in Bosnia and Herzegovina“ will analyze how political parties exploit institu-tional weaknesses, ethnic nationalism, and legislative bodies to maintain their political power, while simultaneously undermining the fundamental principles of the rule of law and democracy in Bosnia and Herzegovina. The analysis will focus on institutional weakness as a key factor enabling politi-cal elites to manipulate the state apparatus. The political system of Bosnia and Herzegovina, established by the Dayton Peace Agreement, has become a tool in the hands of political parties that exploit fragmented and inefficient institutions to remain in power. Instead of serving the citizens, institutions, including the judiciary and state administration, have become instruments of political parties.